Automation tools for web testing: beyond selenium - Segovia González, Rosario (2022)
In today’s fast-paced world of software development, automation test tools proved to be of great importance in building a robust product while delivering quality software faster. To keep up with everchanging demand, organizations are embracing test automation. The goal of automation test tools has shifted from shortening test times to better coverage and effective use of test cases. Selenium is a familiar, longstanding, and well-known name in the market of test automation. It is considered the industry standard for web application user interface automation testing. But as it happens most of the time, it also has certain limitations. There are other test-automation systems with good features available in the market. The goal of this article is to review and analyze them as a Selenium alternative